2000
DOI: 10.1111/j.1749-6632.2000.tb06487.x
|View full text |Cite
|
Sign up to set email alerts
|

Body Composition Measurements during Infancy

Abstract: Infancy is the period of most rapid postnatal growth and is accompanied by major changes in body composition (BC). There are many challenges to successfully measuring BC of infants in vivo, which include the inherent limitations in the underlying assumptions for each technique. The small body mass and rapid nonuniform changes in body parts, that is, the components of BC during infancy, can strain the technical limits of all methods. Many techniques for in vivo BC measurement used in older people have been appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 53 publications
1
28
0
Order By: Relevance
“…It is relatively easy to improve the postnatal weight gain of preterm babies with additional energy in the form of glucose polymers or fat added to enteral feeds, but this may only increase fat mass rather than the intended increase in lean body mass (35,36). At present, simple anthropometric measurements using all three growth parameters and not just weight are the most reliable and readily available growth parameters for preterm babies (37).…”
Section: Recommendationsmentioning
confidence: 99%
“…It is relatively easy to improve the postnatal weight gain of preterm babies with additional energy in the form of glucose polymers or fat added to enteral feeds, but this may only increase fat mass rather than the intended increase in lean body mass (35,36). At present, simple anthropometric measurements using all three growth parameters and not just weight are the most reliable and readily available growth parameters for preterm babies (37).…”
Section: Recommendationsmentioning
confidence: 99%
“…With the older but most widely used pencil beam DXA technique in the study of small subjects, the uncritical acceptance by some investigators of the earlier unvalidated versions of the infant software continues to contribute to the conflicting data in the literature [3,7,8]. Unfortunately, subsequent improvements in the software may not be re-applied to the earlier scans because of differences in scan acquisition technique and non-compatibility of software.…”
Section: Discussionmentioning
confidence: 90%
“…The development of dual energy X-ray absorptiometry (DXA) with its ability to provide simultaneous measurements of the bone, lean and fat mass components of body composition [3] has increased the ability to understand the interaction between nutrition and growth in research and clinical situations involving animals and humans.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that clothes, diapers, and flannel sheets can interfere with DXA measurements of soft tissues (22) and body weight (23). Work done by Brunton et al (5) showed that increasing the number of flannel sheets consistently increases the DXA determined weight by 33% of the measured blanket weight.…”
Section: Flannel Sheets and Milk Ingestionmentioning
confidence: 97%